From Explicit to Implicit Theories of Creativity and Back: The Relevance of Naive Criteria in Defining Creativity. (8th February 2021) - Weisberg, Robert; Pichot, Nicolas; Bonetto, Eric; Pavani, Jean‐Baptiste; Arciszewski, Thomas; Bonnardel, Nathalie
Abstract: The different definitions of creativity that have been proposed by researchers have developed out of what are called explicit theories of creativity, on the basis of logical and semantic arguments, independently of empirical data. The present paper focuses on two such definitions, the standard definition (M.A. Runco & G.J. Jaeger, 2012), which defines a creative product as one that is novel and valuable, and R.W. Weisberg's (2015, 2018) intentional novelty (IN) definition, which defines a creative product as one that is novel and produced intentionally. Those two definitions make different predictions concerning the criteria that lay‐people will when making judgments of creativity: both emphasize novelty, but the standard definition also includes value, while the IN definition includes the intention of the individual. Three studies ( N  = 983) tested those differential predictions using a scenario method. Overall, the results supported the importance of novelty and intentionality in lay‐people's judgments of creativity, as well as raising questions about the role of value in such judgments. That pattern of results supported the IN definition. However, the results did not support the specific predictions made on the basis of the IN definition. The theoretical implications are discussed.